Determinants of crime in Malaysia: evidence from developed states - Ishak, Suryati; Mhd Bani, Nor Yasmin (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Despite the alarming statistics and growing concerns over crime, the study of crime in Malaysia has received little attention and is largely neglected by the literature on crime in general. Thus, this study is an attempt to add to the existing literature on crime research in developing countries, specifically, in Malaysia. This study aims to determine the socioeconomic and socio-demographic determinants of crime in four developed states of Malaysia from 1990 to 2008. The study utilises fixed effects to examine the determinants of crime in selected states. The findings reveal that GDP per capita, unemployment rate, population density and the number of police officers are significant determinants of total and property crime. On the other hand, violent crime is determined by population density and number of police officers only. The robustness test shows that both population density and the number of police officers are the determinants of property and violent crimes.